PENGEMBANGAN WISATA TERPADU BERBASIS ENTREPRENEURSHIP OLEH BUMDES MUGIBANGKIT - sri nathasya Br Sitepu (Jurnal Bakti Masyarakat Indonesia, 2021)
assistance is carried out by lecturers at the Faculty of Business Management and lecturers at the Faculty of Architecture, Ciputra University, Surabaya. Assistance was given to all managers of the Mugibangkit BUMDES. Assistance is provided through five stages, namely: a) observation of the condition of the Mugibangkit BUMDES, b) potential exploration, c). socialization of the concept of entrepreneurship, d), execution of integrated tourism development, e) evaluation of integrated tourism development. Assistance to BUMDES managers provides benefits from educational and economic aspects. The benefits of education are in the form of increased entrepreneurial knowledge and the ability to create business units. Benefits from the economic aspect include the successful development of a new business unit (Integrated Tourism) as one of the business units in the Mugibangkit BUMDES.Pendampingan ABSTRAK:pengembangan wista terpadu berbasis entrepreneurship dilakukan dosen Fakultas Manajemen Bisnis dan dosen Fakultas Arsitektur Universitas Ciputra Surabaya.  Pendampingan diberikan kepada seluruh pengelola BUMDES Mugibangkit. Pendampingan diberikan melalui lima tahapan yaitu:  a) observasi kondisi BUMDES Mugibangkit, b) penggalian potensi, c). sosialisasi konsep entrepreneurship, d), eksekusi pengembangan wisata terpadu, e) evaluasi pengembangan wisata terpadu. Pendampingan kepada pengelola BUMDES memberikan manfaaat dari aspek pendidikan dan ekonomi. Manfaat pendidikan berupa peningkatkan pengetahuan entrepreneurship dan kemampuan dalam menciptakan unit bisnis. Manfaat dari aspek ekonomi berupa keberhasilan pengembangan unit bisnis baru (Wisata Terpadu) sebagai salah satu unit bisnis pada BUMDES Mugibangkit.